The Impact of COVID-19 Pandemic on Selected Sectoral Stock Returns in Malaysia - Wei Jie, Lee; Venus Khim-Sen, Liew; Shirly Siew-Ling, Wong (Universiti Malaysia Sarawak, 2025)
The COVID-19 pandemic that happen in year 2020 brought massive impact in worldwide including Malaysia. The global stock market was affected due to the COVID-19 pandemic. The purpose of this study is to determine the impact of the COVID-19 pandemic on sectoral stock return in Malaysia by using time series analysis. This study employed Ordinary Least Squares (OLS) estimation to determine the impact of the COVID-19 pandemic. The data collected are daily data. The Kuala Lumpur Composite Index (KLCI), financial sector (KLFI), healthcare sector (KLHC) and telecommunication sector (KLTC) are the dependent variable in this study. The independent variables are divided into two categatories which are the COVID-19 variables and the control variables. The COVID-19 variables include the confirmed cases, death cases, recovery cases, lockdown policy, and vaccination while the control variables include the gold price, the oil price, the exchange rate, the volatility index and the NASDAQ composite index. The Granger causality test was developed to determine the short-run causality between those surveyed variables. The result showed that the COVID-19 variables significantly impacted the selected sectoral stock indices and major indices in Malaysia. Therefore, a suitable policy and lockdown measure is essential to minimize the negative impact of COVID-19 pandemic on Malaysian stock market.